2002
DOI: 10.4314/wsa.v28i2.4880
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of soybean peroxidase treatment of 2, 4-dichlorophenol

Abstract: In the presence of hydrogen peroxide (H 2 O 2 ), peroxidase enzymes (PE) catalyse the oxidation of various chlorinated phenols to free radicals, which then combine to form insoluble polymers that precipitate out of solution. This study systematically characterises the treatment of 2,4-dichlorophenol (2,4-DCP) using soybean peroxidase (SBP) as an oxidising catalyst. The effects of pH, SBP concentration, polyethylene glycol (PEG) additive and initial chlorophenol concentration on 2,4-DCP treatments are reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
(6 reference statements)
3
10
0
Order By: Relevance
“…For this reason, the enzyme used for phenol removal was incubated with an activatory concentration of Ni 2+ (2 mM). Similar results were reported for the effect of PEG on HRP stability [8][9][10][11][12]. In such a process, peroxidase can be inactivated by several mechanisms: I) Adsorption of polymerized phenol on peroxidase resulting in reduced access of a substrate to the enzyme's active site [30][31][32].…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…For this reason, the enzyme used for phenol removal was incubated with an activatory concentration of Ni 2+ (2 mM). Similar results were reported for the effect of PEG on HRP stability [8][9][10][11][12]. In such a process, peroxidase can be inactivated by several mechanisms: I) Adsorption of polymerized phenol on peroxidase resulting in reduced access of a substrate to the enzyme's active site [30][31][32].…”
Section: Methodssupporting
confidence: 71%
“…E-mail: nazarikh@ripi.ir be considered, and various techniques for reducing the role of suicide inactivation must be applied. Among such methods, the use of polyethylene glycol (PEG, with various molecular weights) has been reported to increase the stability and lifetime of the enzyme [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature at which optimum activity was attained (30°C) is close to that found for BGP and HRP (Akhtar et al 2005;Bódalo et al 2006;Yamada et al 2007), which lied between 30°C and 40°C, and somewhat lower than TMP that showed an optimum between 40°C and 50°C (González et al 2006). By contrast, SBP has been reported to be much more active at 22 than at 4°C (Kennedy et al 2002), while other studies demonstrated that SBP is even more active at 80°C than at 20°C (Geng et al 2001).…”
Section: The Effect Of H 2 O 2 Ph and Temperaturementioning
confidence: 77%
“…Horseradish peroxidase is the most studied enzyme in this regard, and has been used mainly for the treatment of aqueous phenols and chlorophenols (Tatsumi et al 1996;Wu et al 1997;Tong et al 1998;Wagner and Nicell 2002;Cheng et al 2006;Dalal and Gupta 2007), but also other pollutants such as polychlorinated biphenyls (Singh et al 2000) and bisphenol A (Huang and Weber 2005). Crude and partly purified soybean peroxidase has also been used in the treatment of phenols and chlorophenols (Caza et al 1999;Flock et al 1999;Wilberg et al 2002;Kennedy et al 2002), and bitter gourd (Momordica charantia) peroxidase for the treatment of textile dyes (Akhtar et al 2005).…”
mentioning
confidence: 99%
“…Recently, however, peroxidase from other sources such as soybean (Caza, Bewtra, Biswas, & Taylor, 1999;Kinsley & Nicell, 2000;Kennedy, Alemany, & Warith, 2002) and turnip (Duarte-Vazquez, Ortega-Tovar, Garcia-Almendarez, & Regalado, 2003), have been suggested as alternatives to horseradish. The peroxidase treatment process is still in the experimental stage.…”
Section: Removal Of Phenolic Contaminants and Related Compoundsmentioning
confidence: 98%